The Solomon curse [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Fargo adventures., 2015)
Journeying to the Solomon Islands to hunt for treasure linked to myths about ancient atrocities, Sam and Remi Fargo follow leads to Australia and Japan, where they make a wonderful but monstrous discovery.